Revision of the Old World species of the genus Tephritis (Diptera, Tephritidae) with a pair of isolated apical spots - Korneyev, Severyn V.; Korneyev, Valery A. (Zootaxa, 2019)
Species of the genus Tephritis usually have the wing pattern with dark rays on veins R4+5 and M connected to the preapical dark spot or to each other (often called the “apical fork). Some species, however, have a solid apical crossband (Korneyev, 2013), whereas others have an isolated pair of apical spots. Specimens with the latter morphological character occasionally occur in many species with typical wing patterns, but in this article we focus on the species that normally have it. They occur mostly in the Palaearctic Region, except T. candidipennis Foote, 1960 from North America. A total of twenty species are recognized in this complex, including three new species and two new subspecies: Tephritis arsenii S. Korneyev, 2015, T. bardanae (Schrank 1803), T. conyzifoliae Merz 1992, T. crepidis Hendel 1927, T. dilacerata (Loew 1846), T. dilacerata kaszabi new subspecies, T. formosa (Loew 1844), T. ghissarica new species, T. hendeliana Hering 1944, T. hyoscyami (Linnaeus 1758), T. kyrghyzica new species, T. kogardtauica Hering 1944, T. kovalevi Korneyev & Kameneva 1990, T. kovalevi kumana new subspecies; T. postica (Loew 1844), T. stictica Loew 1862, T. theryi Séguy 1930, T. tridentata S. Korneyev & Mohamadzade-Namin 2013, T. truncata (Loew 1844), T. valida (Loew 1862), T. youngiana new species, and T. zernyi Hendel 1927. Most of the species are keyed, redescribed and illustrated based on extensive material from the Palaearctic Region. Lectotypes of T. dilacerata, T. formosa, T. hendeliana, T. truncata, T. valida, T. posis, T. heiseri, T. procera and a neotype for T. postica are designated. Known host plants of this complex belong to the tribes Anthemideae, Cardueae, Cichorieae, Inuleae, and Senecioneae (Asteraceae); preliminary comparison of the morphological characters (other than the wing pattern) with the distribution among host plants shows that the flies apparently do not form a monophyletic group, belonging to several different lineages, which also include other species with the typical “forked wing pattern. New distribution records and host plants are reported.        The following synonymies are established: Musca hyoscyami Linnaeus 1758 = Tephritis heiseri Frauenfeld 1865 new synonym; Trypeta postica Loew 1844 = Tephritis posis Hering 1939 new synonym.